1990
DOI: 10.1021/ac00222a015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of aromatic and sulfur-containing amino acids, peptides, and proteins using high-performance liquid chromatography with photolytic electrochemical detection

Abstract: Aromatic amino acids, sulfur-containing amino acids, peptides containing such constituents, and proteins can now be detected in high-performance liquid chromatography by the use of on-line, postcolumn, continuous photolytic derivatization with electrochemical (HPLC-hv-EC) detection. The overall approach is a very simple, reproducible, rapid, and fully automatable approach for the determination of certain amino acids, peptides, and proteins with excellent selectivity, sensitivity, and linearities of response. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Various important LC methods for amino acid, peptide and protein analysis were reviewed and evaluated 126,127 . A review of HPLC methods for the analysis of selected biogenic amines in foods appeared, including methods for extraction and for elimination of interfering compounds 128 .…”
Section: Generalmentioning
confidence: 99%
“…Various important LC methods for amino acid, peptide and protein analysis were reviewed and evaluated 126,127 . A review of HPLC methods for the analysis of selected biogenic amines in foods appeared, including methods for extraction and for elimination of interfering compounds 128 .…”
Section: Generalmentioning
confidence: 99%
“…Theoretically, the peptides containing electroactive amino acids, such as tyrosine (Y), tryptophan (W), methionine (M), and cysteine (C), show EC responses without photolysis (lamp off), and the peptides containing phenylalanine (F) should have EC responses after photolysis [36]. Therefore, two new peaks should be shown and three existing peaks should be increased in their sensitivity in tryptic peptide mapping after photolysis ( Table 2).…”
Section: The Application Of Photolysismentioning
confidence: 99%
“…It has been shown that some polypeptides can be detected by their free amino (NH,) group [38] or by the presence of the phenol group of tyrosine (tyr) or the indole group of tryptophan (trp) [39], methionine (met), and cysteine (cys). The use of photolytic reactions [35][36][37]431 and chemically modified electrodes [44] has extended the application of electrochemical detection [45]. Initial stuches showed that peptides could be detected by modifying them with electroactive substituents such as 3,G-dinitrophthalic anhydride [ 461.…”
mentioning
confidence: 99%
“…Photolysis may be used to convert a substance into more readily detected products, for example, the introduction of fluorescence or electrochemical activity [552,641,649,657,[659][660][661][662][663]. Photolysis may be used to convert a substance into more readily detected products, for example, the introduction of fluorescence or electrochemical activity [552,641,649,657,[659][660][661][662][663].…”
Section: Reaction Detectorsmentioning
confidence: 99%